Delineation of flood inundation extent as the result of land use changes in Kuantan River Basin - Ng, Zone Fhong (2021)
Flood is undoubtedly the most devastating natural disaster in Malaysia. Flood induced problems such as loss of life, property damages, and infrastructure disruptions have distressed the local authorities and government agencies in Malaysia including the Kuantan District. One of the worst floods that occurred in Kuantan took place in December 2013 which was caused by extreme monsoon rain. This massive flood resulted in the evacuation of around 14,044 people and major damages to the electricity, road structure, buildings, and properties. Although flood event happens in a yearly basis in the Kuantan River Basin (KRB), there are still lack of flood risk management studies conducted in this region. Hence, a comprehensive flood study, especially the generation of flood inundation map (FIM) in (KRB) is highly needed for the future urban planning purpose. This study aims to simulate the flood hydrograph based on extreme rainfall events, and to develop the FIM for KRB. Watershed and river networks of the KRB were delineated from the Shuttle Radar Topography Mission Digital Elevation Model (SRTMDEM) with a resolution of 30 m using ArcGIS application. ArcGIS integrated application, the Geospatial Hydrologic Modelling Extension (HEC-GeoHMS) was used to extract the hydrological parameters as the input for the hydrological modelling. For the rainfall-runoff analysis, the SCS Unit Hydrograph transformation method and SCSCN loss method were implemented in the Hydrologic Modelling System (HEC-HMS). Runoff results from the hydrological model were then applied in the 1D-2D River Analysis System (HEC-RAS) for the unsteady-flow simulation to simulate and predict the river water level and overbank flow which were subsequently used to generate FIM. The flood hydrographs that have been simulated from the hydrological modelling was compared with the observed data. After the process of calibration and validation, it was noted that the simulation produced the same pattern of flow discharge to the observed with an average Nash Sutcliffe efficiency, NSE of 0.641 and Root Mean Square Error, RMSE of 70.9 m³/s. For the result of the 1D hydraulic modelling, it indicates that the water levels simulated at the upstream and downstream of the Kuantan river was fitted with the observed levels with an average E of 0.716 and RMSE of 0.493 m. Meanwhile, for the 2D hydraulic modelling, the generated flood inundated areas in the year 2013 demonstrates almost 70% similarity to the observed flood areas. The flood extent using land use in year 2013 is almost 50% larger compared to that in year 2010 . Based on the modelling analysis and outcome, it can be concluded that generation of flood hydrograph and flood inundation extent is sufficient by SRTM-DEM in hydrological and hydraulic modelling.